Promises of Music in Education? - Tervaniemi, Mari; Tao, Sha; Huotilainen, Minna (Frontiers in Education, 2018)
Learning in school is intended to help students master academic skills such as reading, writing, and mathematics, as well as to acquire knowledge about different subjects such as history, geography, biology, and so on. However, in the future, successful learning will be largely manifested by students' global and transferable skills, such as analytical thinking, problem solving, collaboration, and social skills. Here we explore the promises of using music to support learning in the future. We review empirical evidence on the effects of music learning on neurocognitive development in children in formal and informal settings, in music interventions, and also in community settings. With this review, we wish to stimulate discussion about the roles that music could play in promoting learning in schools and elsewhere.